Illegal, immoral, fattening or what?: How deterrence and responsive regulation shape tax morale - Lars P. Feld; Bruno S. Frey (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2004)
The traditional economic approach to tax evasion does not appear to be particularly successful in explaining the extent of tax compliance. It is often argued that reciprocity norms which establish a fiscal exchange between the state and the citizens shape tax morale to a large extent. In that respect, a case study of Switzerland may be useful because the small size of the cantons and their direct democratic political systems procedurally establish a close exchange relationship between taxpayers and tax authorities. In this paper, evidence is discussed on how tax morale in Switzerland evolved over time. In addition, the impact of economic, legal, socio- demographic, psychological and institutional factors on Swiss tax evasion is analyzed. It can be concluded that Switzerlands system of responsive regulation increases tax morale.
Keywords: H26; H73; D73; D78; 330; Tax Evasion; Tax Morale; Deterrence; Responsive Regulation; Steuermoral; Demokratie; Bürgerbeteiligung; Schweiz